Can the digital economy foster advancements in the healthcare sector? — a case study using interprovincial data from China - Zhengqi Wei; Keke Wei; Jing Yang; Meilin Zhang; Feng Yang (BMC Public Health)
Abstract Background As China's "Internet + Health" initiative advances, the digital economy significantly influences the quality of medical and health services. However, there is a research gap concerning the digital economy's specific impacts, mechanisms, and marginal effects on these services. This gap impedes a comprehensive understanding of the digital economy's potential in healthcare. Aims This study aims to clarify the digital economy's impact mechanisms on medical and health services levels, offering a scientific foundation for more targeted and effective policy formulation, thereby fostering sustainable digital development in healthcare. Methods Utilizing panel data from China's 31 provinces (2011–2020), this paper employs the Spatial Durbin Model to analyze the spatial and marginal effects of the digital economy on healthcare service levels. To ensure analysis accuracy and robustness, the study refines the spatial weight matrix and addresses model endogeneity using the Generalized Spatial Two-Stage Least Squares method. Additionally, it examines regional disparities in the digital economy's impact through SDM and explores intermediary mechanisms and threshold effects using a mediation effect model and a panel threshold model. Results Findings indicate that the digital economy positively affects medical and health services in both local and neighboring regions, with variations across areas. The eastern region particularly benefits from the digital economy's enhancement of service levels, while the central and western regions see less impact. The digital economy enhances services by improving medical resource levels and promoting their coordinated development. However, this positive effect is moderated by the digital economy's and the region's economic development levels, with more pronounced impacts in regions with higher digital and economic development. Conclusions The digital economy plays a crucial role in improving medical and health services, and its full potential is beneficial for the industry's advancement and sustainability. Nonetheless, addressing the uneven digital economy development across regions is essential to ensure equitable benefits for all areas.